Zagadnienia dowodzenia w postępowaniu podatkowym a materiał postępowania karnego - Kanty, Tomasz (Kwartalnik Prawa Podatkowego, 2016)
The article concerns the principles of proving in tax proceedings, with particular emphasis on the rules governing the inadmissability of evidence and utilizing materials collected in a criminal trial. The author attempts to transpose the theory of inadmissability in a criminal trial to tax proceedings. He also seeks to demonstrate the impact of the inadmissability on the transposition of the material collected in criminal proceedings.